2005
DOI: 10.1111/j.1440-1681.2005.04189.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Glut‐4 Null Mice to Study Skeletal Muscle Glucose Uptake

Abstract: 1. The present review focuses on the effects of varying levels of GLUT-4, the insulin-sensitive glucose transporter, on insulin sensitivity and whole body glucose homeostasis. 2. Three mouse models are discussed including myosin light chain (MLC)-GLUT-4 mice which overexpress GLUT-4 specifically in skeletal muscle, GLUT-4 null mice which express no GLUT-4 and the MLC-GLUT-4 null mice which express GLUT-4 only in skeletal muscle. Overexpressing GLUT-4 specifically in the skeletal muscle results in increased ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
(147 reference statements)
0
11
0
Order By: Relevance
“…Fam and coworkers (2012)showed that the deletion of the skeletal muscle GLUT4 on the pure C57BL6/J background strain did not impair the whole-body glucose disposal. These authors, among others (Ryder et al 1999, Charron et al 2005, Fam et al 2012, considered that other unidentified GLUTs were upregulated in an attempt to compensate the lack of GLUT4. Probably, the previous hypothesis justifies the fact that even with lower content of plasma membrane GLUT4 in EDL and soleus, the OTR/down group did not exhibit lower glycogen concentrations when compared with the CT group (Pereira et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Fam and coworkers (2012)showed that the deletion of the skeletal muscle GLUT4 on the pure C57BL6/J background strain did not impair the whole-body glucose disposal. These authors, among others (Ryder et al 1999, Charron et al 2005, Fam et al 2012, considered that other unidentified GLUTs were upregulated in an attempt to compensate the lack of GLUT4. Probably, the previous hypothesis justifies the fact that even with lower content of plasma membrane GLUT4 in EDL and soleus, the OTR/down group did not exhibit lower glycogen concentrations when compared with the CT group (Pereira et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, why insulin deficiency in Gcgr -/-mice does not appear to alter fat or muscle metabolism is unclear. It is worth noting that glucose tolerance is not altered in muscle-specific insulin receptor KO mice (83) or in whole-body Glut4-null mice (84). In the normal dog and human, on the other hand, when insulin and glucagon secretion were simultaneously made deficient using somatostatin (30,85), insulin lack resulted in a significant decrease in glucose clearance and a consequent doubling of the plasma glucose level.…”
Section: Glucagonocentrism: Insulin Actions Are Mediated By Glucagonsmentioning
confidence: 99%
“…While we did not directly measure glucose uptake in vitro in these specific muscle types from our KO mice, the evidence presented by these earlier studies support our idea of the existence of novel GLUT4-independent transporter system(s) (Ryder et al 1999a, Charron et al 2005. However, neither these early studies nor our own have identified these potential transporters.…”
Section: Discussionmentioning
confidence: 54%
“…The disposal of glucose into muscle and adipose tissue is dependent on the action of specific glucose transporters (GLUT) and the hormonal regulation of their expression and function (Charron et al 2005). The Glut4 (Slc2a4) is the main insulin-responsive transporter abundantly expressed in skeletal muscle, adipose tissue and heart (Kahn 1992, Mueckler 1994.…”
Section: Introductionmentioning
confidence: 99%